Hybrid shop system of plant and aquarium. Issue 5 (4th July 2021) - Chiu, Min-Chie; Cheng, Ho-Chih; Yeh, Long-Jyi; Kao, Chen-Tang; Chiu, Che-Min
Abstract: A hybrid plant and aquarium system can save water via water circulation and filtering. In order to conveniently seed and harvest and breed in the aquarium, the system is a module. The seeding/harvesting and breeding can be easily separated or combined. A filtering net is installed at the bottom of the container. The system can serve as a factory for planting, for aquarium breeding, or serve as an ornamental farm. All the traditional environmental sensing (a thermal sensor, a humidity sensor, a luxmeter, a soil moisture sensor, a ph meter, and an oxygen sensor) and controlling devices (a heating bulb, a LED, a feeder, a fan, a sound-proofing curtain, an air supply, and a water sprayer) for a green house and aquarium are included in the system. The microcontroller of Arduino UNO is adopted in the system. In addition, green energy devices such as solar board and wind generator are also used. Finally, this invention can also generate green electricity and facilitate water circulation and filtering. Because of this, both water and fertilizer can be saved.